Saving Tendency of Developed and Developing European Countries - Arıç, Kıvanç Halil; Sek, Siok Kun (Ekonomika, 2021)
In the previous literature studies, the saving condition is mainly examined focusing in Developing countries and Asian countries. The examination on the saving condition is crucial due to the linkages between saving accumulation and economic growth. The studies that focused in Developed countries are limited. This study extends the analysis by comparing the saving determination in Developed and Developing European countries and contributes to the literature of saving in two ways. First, the study compares the two panel groups, Developed and Developing European countries, which might reveal how economic development could affect the saving behavior. Second, the study considers the cross-section dependency effect in the panel data analysis by applying the testing (second-generation panel unit-root and cointegration tests) and the estimation approaches (Augmented Mean Group, AMG estimator). The study demonstrates that ignoring the cross-section dependency effect might lead to misleading results. Four determinants of savings are examined (GDP per capita, age dependency ratio on working group, inflation and government expenditure). Our results reveal the existence of cointegration and cross-section dependency in the saving relationship in both panel groups. Comparing the results across panel groups, it is observed that government expenditure is contributes to lower saving in both groups of countries with larger impact in the Developed European countries. On the other hand, GDP contributes to higher saving in both groups of countries. Inflation also leads to higher saving in the Developed group but not in the Developing group.   Age dependency ratio is not influential in the Developed group but might trigger lower saving in the Developing group.
Keywords: saving; economic growth; European countries; cross-section dependency; panel data